Granting Dispensation To Children Who Marry Underage After The Enactment Of Law Number 16 Of 2019 (Decision Number 157/Pst.P/2020/Pa.Sbr) - Resia Monika; Benny Djaja (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Underage marriage is an event that is considered normal by some people in Indonesia and other countries, but underage marriage can become an issue that attracts public attention and can continue to become a legal case in Indonesia, Law Number 16 of 2019 regarding amendments of Law Number 1 of 1974 in article 7 paragraph (1) states that men and women can marry if they have reached the age of 19 years and in paragraph 2 states that if men and women have not reached the age specified by law, namely 19 years then parents can ask for Dispensation to the Religious Court. Therefore the formulation of the problem is used to better know and explore how the application of Article 7 paragraph (1) of Law Number 16 of 2019 regarding the granting of dispensations to minors. This research also uses the Normative Juridical Method which uses the library research method and also this research uses a Qualitative Method, Based on the Analysis it can be concluded in the decision of case Number 157/Pst.p/2020/PA.Sbr the judge still grants the request for dispensation because the parents or child have agreed to the granting of the dispensation, so in In his opinion, the judge will grant the dispensation of the minor, even though it is not in accordance with the applicable age provisions in Law Number 16 of 2019 contained in Article 7 paragraph (1).